The Effect Program teaching by use Sign Language supported by Cartoons in teaching and maintaining the performance in free style swimming for deaf-mute (8-10)years - Ahmed, Muthana; Yasin, Lina (Journal of Physical Education, 2015)
The problem with the search in the fact that free-swimming learning for children deaf-mute ages (8-10 years) has not been given enough attention by researchers resulting from the difficulty of communicating with this type of disability and how to harness the sign language in the learning process and this is what I have seen the researcher during her trainer for swimming, so we need to be serious and objective and stop it from going through in this area and prepare the curriculum using sign language to teach deaf-mute children ages (8-10 years) free style swimming to be the nucleus of the national team swim for the deaf in the future. The research objective: put program sign language supported cartoons in teaching and maintaining the performance in free style swimming for deaf-mute (8-10) years and know the effect of program teaching using the Sign Language supported Cartoons in teaching and maintaining the technical performance in free style swimming for deaf-mute (8-10) years. The researchers used the experimental method to design only a posteriori tests of equal group. Was selected research community way intentional children deaf-mute from Hiwa Institute for the deaf-mute in Erbil / Kurdistan province for the year 2014 totaling (17) children ages (8-10 years) of the total asset community and adult (93) children. the number of respondents (12 children). program teaching was the experimental group using the free style swimming (animated). The researcher found the following conclusions: 1. Tutorial for the second group, which used the animation program in a way contributed Positive and effective in learning to swim free of the deaf-mute children ages (8-10) years. 2. Outweigh the second experimental group that used the animation program that was used in the degree program and retain the absolute amount of forget fullness during Learn the technical performance of the free pool for the deaf-mute children ages (8-10) years. The main recommendations were: 1. The need to use animation program in free-swimming education for deaf-mute children ages (8-10) for the years proven by the results of active learning in the technical performance of the free-swimming. 2. Design and produce educational programs using animation to include the rest of the other types of swimming to improve the learning process